INVESTIGASI EKSPERIMENTAL PEMANAS AIR TENAGA SURYA SISTEM TRICKLE BERBAHAN POLIKARBONAT VARIASI LAJU ALIRAN 2 LPM - Alisya Eka Putri; Nugroho Agung Pambudi; Husin Bugis (Nozel : Jurnal Pendididikan Teknik Mesin, 2023)
Solar energy is one of the most impactful renewable energy sources and has great potential compared to other energy sources. The use of solar energy can be maximized by using solar panel technology and solar collectors. One example is a solar water heater. Polycarbonate is a good material to be applied to solar water heaters because it has good mechanical properties and is corrosion resistant. This study aims to analyze the performance of a polycarbonate solar water heater with a trickle system using a flow rate of 2 l/m. This type of research is quantitative with experimental research methods. This research was conducted by flowing water through a solar water heater and taking data from 08.00-15.00 with 3 repetitions to obtain accurate results. Data were collected by recording the temperature at the inlet, outlet, collector, top collector, environment, intensity of solar radiation, and wind speed. The data obtained were analyzed to find collector efficiency, fluid efficiency and total efficiency. Based on the research results, this solar water heater is capable of producing water temperatures up to 40.5°C with temperature changes of up to 7.2°C. This solar water heater is able to produce a collector efficiency of up to 52%, and a total efficiency of 37%.